1978
DOI: 10.2307/1142398
|View full text |Cite
|
Sign up to set email alerts
|

Law and Punishment in Early Renaissance Venice

Abstract: Existing capitularies, though they report a few important parti from the fourteenth-century, seem to concentrate primarily on texts from the fifteenth and sixteenth centuries. The main exception to this later orientation is the capitulary for the Signori di Notte. See N. MOCENIGO, CAPITOLARE DEI SIGNORI DI No'i-rI' ESIS-TANTE NEL CIVICO MusEo DI VENEZIA (1877). The early entries of judicial capitularies were edited. See LE MAG. Is'rRA'rURE GIUDICIARIE VENEZIANE E I LORO CAPITO-LARE FINO AL 1300, in MONUMENTI S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although somewhat less thoroughly covered than the other areas, Italy is the fifth region with a series of studies that permit empirically based extrapolations. Studies of medieval and renaissance cities include Bologna (Blanshei 1981(Blanshei , 1982, Florence (Becker 1976), and Venice (Ruggiero 1978(Ruggiero , 1980. Romani (1980) has examined court records in late sixteenth-century Mantova, and a fascinating study by Blastenbrei (1995) analyzes wounding reports by medical professionals and judicial records in late sixteenth-century Rome.…”
Section: A Sources: History Of Homicide Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Although somewhat less thoroughly covered than the other areas, Italy is the fifth region with a series of studies that permit empirically based extrapolations. Studies of medieval and renaissance cities include Bologna (Blanshei 1981(Blanshei , 1982, Florence (Becker 1976), and Venice (Ruggiero 1978(Ruggiero , 1980. Romani (1980) has examined court records in late sixteenth-century Mantova, and a fascinating study by Blastenbrei (1995) analyzes wounding reports by medical professionals and judicial records in late sixteenth-century Rome.…”
Section: A Sources: History Of Homicide Databasementioning
confidence: 99%
“…Only to the degree that overall levels of violence fell throughout the early modern age did violence become correlated with class. Ruggiero (1980) has done probably the most thorough analysis of the social status of premodern violent offenders. In a detailed study of violence in Venice between 1324 and 1406, he was able to identify the social standing of more than 1,600 offenders dealt with by the secular judicial authorities.…”
Section: Social Status Of Offendersmentioning
confidence: 99%
“…The secular pattern in Italy, however, diverges decisively from the trend found for northern Europe. There exist isolated estimates for a number of Italian cities, such as Bologna (Blanshei 1982), Florence (Becker 1976), Mantova (Romani 1980) and Venice (Ruggiero 1978), whereby Florence shows the absolute highest homicide rate with 150 homicides per population of 100,000 in the fourteenth century. Blastenbrei (1995) provides homicide rates of 30 to 80 per 100,000 for Rome in the sixteenth century.…”
Section: Italymentioning
confidence: 99%
“…In an article from early in his career, Guido Ruggiero (1978) suggested that banishment as a form of punishment was uncommon in Venice in the premodern period, due to the loss of a contributing member of a society that had "a labor-hungry merchant marine and nascent industrial development" generated by such a sentence (p. 254). But for an alchemist like "Cristoforo di Parigi," who would not contribute, in the eyes of some of the members of the merchant oligarchy that governed the city, to the lifeblood of the Venetian economy and society and, in fact, whose activities poisoned it, banishment was a far more merciful option than outright execution.…”
mentioning
confidence: 99%